ADAKAH PENGARUH "EVA" TERHADAP NILAI PERUSAHAAN DAN KEMAKMURAN PEMEGANG SAHAM PADA PERUSAHAAN PUBLIK? - R. Agus Sartono; Kusdhianto Setiawan (Journal of Indonesian Economy and Business (JIEB), 1999)
Economic Value Added (EVA) as a performance measure has proven in United States as prominent measure of companies business performance, especially in focusing on business operation that fit with its' core business. However, our research found that EVA has no significant correlation with MVA (Market Value Added) and abnormal return as indicators of stock price movement, but EVA significantly associated with leverage that support Modigliani-Miller theory of capital structure in its' second proposition. These findings rise the question whether or not EVA could be used as effective performance measure in Indonesia and than use it as a mean of management incentive in order to align with shareholders objective to maximize value of the firm.